Chilli hotness determination based on optical capsaicin biosensor using stacked immobilisation technique - Rosmawani Mohammad; Musa Ahmad; Lee Yook Heng (2014)
The fabrication of an optical biosensor based on stacked immobilisation of 3-methyl-2-benzothiazolinone hydrazone (MBTH) in sol–gel/butyl acrylate hybrid film and horseradish peroxidase (HRP) in chitosan film for capsaicin detection was studied. The optimum volume ratio of sol–gel to butyl acrylate was 1:0.5 (v/v). Peroxidase was immobilised in chitosan film deposited on top of the hybrid sol–gel/butyl acrylate film containing MBTH. The reaction between capsaicin and MBTH in the presence of HRP and hydrogen peroxide as oxidative agent was studied. The finding indicated that HRP catalysed the oxidative coupling reaction between MBTH and capsaicin thus producing red-coloured azo-dye compounds that could be observed at the wavelength of 505 nm. The colour intensity of the product was found to increase in proportion to the capsaicin concentration after 20–30 s of exposure. The linearity of the biosensor towards capsaicin was in the concentration range of 0.2–4.0 mM with detection limit of 0.17 mM. Relative standard deviation (RSD) values of reproducibility were 5.57–6.33%. The developed biosensor correlated well with the standard method, HPLC for the determination of capsaicin concentration in real samples.